Plant Spacing Implications for Grafted Grapevine I. Soil Characteristics, Root Growth, Dry Matter Partitioning, Dry Matter Composition and Soil Utilisation - Hunter, J.J. (South African Journal of Enology and Viticulture, 2017)
Six plant spacings (3 x 3 m, 3 x 1,5 m, 2 x 2 m, 2 x 1 m, 1 x 1 m, 1 x 0,5 m) were evaluated for their effect on aboveground and subterranean growth, dry matter partitioning and dry matter composition of different plant parts of vertically trellised Vitis vinifera L. cv. Pinot noir vines grafted onto rootstock 99 Richter. The vines were pruned to six buds/m2 soil surface area and supplementary irrigated just after pea berry size and veraison stages. Root distribution was studied by using the profile wall method and by excavating the whole plant. Apparently higher bulk densities occurred in the top soil layers of closer spacings. In the case of fine ( < 0,5 mm), extension (0,5 • 2 mm) and permanent (2 - 5 mm) roots, closer spaced vines significantly compensated in terms of root number per profile wall area. Higher root densities occurred with closer spacing. Aboveground and subterranean growth of the closerspaced vines were reduced; a distinction between in-row spacings of 1,5 m and wider and those 1 m and narrower occurred. Aboveground and subterranean growth were positively related. The angle of root penetration and size of the root system increased with wider spacing. The spread of the root system was apparently not affected by either inter-row or in-row spacing. The majority of roots were located within the allocated in-row distance. Cane and root mass and total vine dry mass per m2 soil surface indicated optimum utilisation of soil volume for medium-spaced vines (2 x 2 m, 2 x 1 m). Evidently higher starch concentrations occurred in the cordons, trunks and roots of widerspaced vines. Roots contained the highest starch concentrations, followed by the trunk, cordon, canes and rootstock trunk. Starch contents of aboveground and subterranean plant parts were similar. The ratio of aboveground:subterranean starch content was, however, lower for closely spaced vines.